Electronic spy bug / Junainah Mohd Daud & Noraini Ismail - Mohd Daud, Junainah; Ismail, Noraini (2015)
Electronic Spy Bug or FM Transmitter is a device designed for purpose of spying or monitoring a selected room in order to gain or collect information secretly. The purpose of spying depends on the person who using it. Some designs of electronic Spy Bug are complicated to be made and some are not. Complicated here means, it has a lot of components in the circuit which cause the size of spy circuit becomes obvious to be seen and not very suitable used in spying. The simple design of spy bug circuit however cannot be sure whether it will function unless it is being made properly. In this project, Electronic Spy Bug was being made based on the wired Spy Bug circuit. This project being simulate using Proteus 8.0 software and the size of the circuit should be a size of thumb-drive. The projects expect to look like as state before. However the result once the project being get through are first is the problem with software where the simulation cannot be run due to lack component model in the software, second the circuit not function well do frequency failure and lastly the size of the circuit are as big as the size of hand-phone charger. Another circuit added is FM Receiver to replace a FM Radio since the range frequency of the Spy Bug circuit not in FM Range which is between 88MHz until 108MHz. From this research, the things found out that affect the changes in frequency are length of the antenna, trimmer capacitor, the number of turns of the coil and the length of the coil.